Analisis Implementasi Regulasi Pangan Hasil Rekayasa Genetika Berbahaya (Studi Putusan Nomor 597/PID.SUS/2022/PN.KTP): Penelitian - Annisa Shafa Kamila; Joko Widarto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Processed food such as alcohol and seedless fruit products produced through genetic engineering require permits related to food safety standards before distribution, due to potential health risks and producers must also comply with existing policies. This research aims to provide an opinion by analyzing legal norms regarding the defendant’s violations. The analysis uses a normative juridical method through legislative and case studies, based on the theory of relative punishment and the theory of justice. The analysis findings identify the judge’s considerations regarding the decision and the imposition of relevant criminal sanctions on perpetrators of health violations, incorporating other research sources as real-life cases. This concludes that the production process must comply with regulations to ensure food content does not cause violation or endanger health.